The Effect of Organizational Citizenship Behavior And Emotional Intelligence On The Psychological Well-Being Of Health Workers With Spiritual Intelligence As A Mediator - Abri; Widhiastuti, Hardani; Dewi, Rusmalia (International Journal Scientific and Professional, 2025)
This study aims to analyze the influence of Organizational Citizenship Behavior (OCB) and emotional intelligence on the psychological well-being of healthcare workers with spiritual intelligence as a mediator variable. The study used a quantitative approach with a sample of 187 healthcare workers at RSUD Beriman Balikpapan selected through a purposive sampling technique. Data were collected using the OCB scale, emotional intelligence, spiritual intelligence, and psychological well-being. Data analysis used Structural Equation Modeling (SEM) with SmartPLS. The results showed that OCB had a positive and significant effect on psychological well-being (β = 0.151; t = 2.063; p = 0.039), as did emotional intelligence (β = 0.437; t = 5.428; p = 0.000). OCB and emotional intelligence also had positive effects on spiritual intelligence (β = 0.414; t = 5.989; p = 0.000; and β = 0.429; t = 6.411; p = 0.000). Spiritual intelligence positively affected psychological well-being (β = 0.280; t = 3.112; p = 0.002). Spiritual intelligence was shown to mediate the influence of OCB (β = 0.116; t = 3.058; p = 0.002) and emotional intelligence (β = 0.120; t = 2.572; p = 0.010) on psychological well-being. These findings underscore the importance of managing organizational behavior and emotional-spiritual capacity to improve the psychological well-being of hospital healthcare workers.